2022
DOI: 10.2196/35178
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Wearable Transdermal Alcohol Sensors: Systematic Review

Abstract: Background There are a range of wearable transdermal alcohol sensors that are available and are being developed. These devices have the potential to monitor alcohol consumption continuously over extended periods in an objective manner, overcoming some of the limitations of other alcohol measurement methods (blood, breath, and urine). Objective The objective of our systematic review was to assess wearable transdermal alcohol sensor accuracy. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…So far, CBIs have varied in their incorporation of evidence-based theory, which limits ability to identify effective components of interventions [ 56 ]. Finally, as the accuracy of transdermal alcohol sensors develops, CBIs can be paired via mobile phone to provide needed on-demand delivery of alcohol treatment [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, CBIs have varied in their incorporation of evidence-based theory, which limits ability to identify effective components of interventions [ 56 ]. Finally, as the accuracy of transdermal alcohol sensors develops, CBIs can be paired via mobile phone to provide needed on-demand delivery of alcohol treatment [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SCRAM samples the air on the skin every 30 minutes. A systematic review of 19 studies that evaluated the use of SCRAM in clinical and nonclinical settings found moderate to high correlations between the transdermal alcohol measurement and self-report ( r = 0.68-0.95) and estimated blood or breath alcohol concentrations (BrAC; r = 0.56-0.99), low malfunction rates (2%), 98.6% sensitivity, and 95.0% specificity for detecting 1 or more standard drink …”
Section: Methodsmentioning
confidence: 99%
“…We calculated the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) and 95% CIs for this cutoff. We chose the SCRAM measure as the primary comparator because it is a purely objective measure of alcohol use with high correlation with alcohol consumption . We conducted similar analyses using self-reported heavy alcohol use as measured by event monitor presses and by AUDIT-C, as defined previously, to determine the robustness of the findings to other metrics of alcohol use.…”
Section: Methodsmentioning
confidence: 99%
“…This protocol has been registered on the Prospective Register of Systematic Reviews (PROSPERO CRD42021231027). On review of the results, it was decided that the findings of this systematic review should be reported in 2 papers: this paper focusing on acceptability and feasibility outcomes and another paper on accuracy outcomes [ 27 ].…”
Section: Methodsmentioning
confidence: 99%